Biomarkers of oxidative stress and protein-protein interaction in chronic obstructive pulmonary disease - Aggarwal, Taru; Wadhwa, Ridhima; Rohil, Vishwajeet; Maurya, Pawan Kumar (Archives of physiology and biochemistry, 2018)
Content: The increased oxidative stress in chronic obstructive pulmonary disease (COPD) patients is the result of increased inhaled oxidants, generated by various cells of the airways. Objective: The investigation included measurements of malondiadehyde (MDA), uric acid, ascorbic acid, and matrix metalloproteinase-12 (MMP-12) in COPD patient. We also performed genetic analysis for protein-protein interaction (PPI) network. Materials and methods: The study was conducted on healthy subjects with normal lung function (NS, 14 subjects) and 28 patients (Global Initiative for Chronic Obstructive Lung Disease (Gold) 1 and Gold 2) with COPD. Results: There was significant (p < .001) increase in MMP-12, MDA and uric acid levels as compared to healthy controls. A significant (p < .001) decline in ascorbic acid level was observed in COPD patients. The PPI was found to be 0.833 which indicated that proteins present in COPD are linked. Discussion and conclusion: This study suggests oxidative stress plays an important role in COPD and the PPI provide indication that proteins present in COPD are linked.